Bounded Rationality and Budgeting - Ibrahim, Mukdad (International Review of Management and Marketing, 2016)
This article discusses the theory of bounded rationality which had been introduced by Herbert Simon in the 1950s. Simon introduced the notion of bounded rationality stating that while decision-makers strive for rationality, they are limited by the effect of the environment, their information process capacity and by the constraints on their information storage and retrieval capabilities. Moreover, this article tries to specifically blend this notion into budgeting, using the foundations of incremental theory introduced by Charles Lindblom by the end of 1950s. The end of discussion shows that the use of intended rationality on public sector organizations will be through of implementing of incremental theory’s rules and procedures. Keywords: Bounded rationality, Budgeting, Incremental Budgeting JEL Classifications: D81 G38 H61